PENGARUH KETERLIBATAN SUAMI DAPAT MENURUNKAN KECEMASAN IBU HAMIL DENGAN MALARIA - Linda Runtuwene; Mardiana Ahmad; Saidah Syamsuddin; Nasrum Massi; Sharvianty Arifuddin; Andi Nilawati Usman (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Objective: This study aims to determine the support / involvement of the husband in the anxiety level of third trimester multigravida pregnant women with mild malaria. Method: The research design used was quasi experimental with pre-test post-test design with a study of 85 respondents with consecutive sampling techniques in three trimester multigravida pregnant women with mild malaria in Timika Health Center, Timika Jaya Health Center, Pasar Sentral Health Center and Wania Health Center in Mimika Regency Papua Province in November - December 2019 using the Hamilton Anxiety Rate Scale (HARS) questionnaire to measure anxiety levels, a husband's support / involvement questionnaire to measure a husband's support / involvement in pregnancy and preparation for cohesion, a questionnaire level of knowledge of malaria sign and danger in pregnancy. Providing education on the signs and dangers of malaria in pregnancy. The analysis of this study uses the Wilcoxon test. Result: statistical test results show that there are differences in anxiety levels in pregnant women with malaria before and after education, with the average score of anxiety levels tending to decrease, moderate and mild anxiety.